Pectin and Zinc Alginate: The Right Inner/Outer Polymer Combination for Core-Shell Drug Delivery Systems - Giulia Auriemma; Andrea Cerciello; Rita P. Aquino; Pasquale Del Gaudio; Bruno M. Fusco; Paola Russo (MDPI AG, 2020)
Core-shell beads loaded with betamethasone were developed using co-axial prilling as production technique and pectin plus alginate as polymeric carriers. During this study, many operative conditions were intensively investigated to find the best ones necessary to produce uniform core-shell particle systems in a reproducible way. Particularly, feed solutions’ composition, polymers mass ratios and the effect of the main process parameters on particles production, micromeritics, inner structure, drug loading and drug-release/swelling profiles in simulated biological fluids were studied. The optimized core-shell formulation F5 produced with a pectin core concentration of 4.0% w/v and an alginate shell concentration of 2.0% w/v (2:1 core:shell ratio) acted as a sustained drug delivery system. It was able to reduce the early release of the drug in the upper part of the gastro-intestinal tract for the presence of the zinc-alginate gastro-resistant outer layer and to specifically deliver it in the colon, thanks to the selectivity of amidated low methoxy pectin core for this district. Therefore, these particles may be proposed as colon targeted drug delivery systems useful for inflammatory bowel disease (IBD) therapy.